A function of social institutions of early childhood education - Eloisa Acires Candal Rocha (Universidade Federal de Santa Catarina, 2003)
Try to explain this text, in my view, essential aspects of the social function of institutions for children's education. The principles and general guidelines for early childhood education that we presents the results of a discussion process to coordinate with the Municipal Department of Education Florianópolis (Division of Child Education) between 2000 and 2001. The aim of the debate was to subsidize the movement of defining guidelines for action for childcare and educational Neise (Centers for Children's Education) of the municipal network. As a starting point, were recovered documents previously produced a guidance curriculum. The idea was to get a deeper understanding to help rewrite the curriculum guidelines of the city, both in the light of experience by educators of the network as a function of the definitions given for early childhood education by more current legislation.